2012
DOI: 10.1097/qad.0b013e32834e1404
|View full text |Cite
|
Sign up to set email alerts
|

Mental health disorders and the risk of AIDS-defining illness and death in HIV-infected veterans

Abstract: Our results demonstrate the high prevalence of mental health diagnoses among HIV-infected veterans. In the era of highly active antiretroviral therapy, presence of psychiatric diagnoses impacted survival and development of ADI. More aggressive measures addressing substance abuse and severe mental illness in HIV-infected veterans are necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 37 publications
2
35
0
Order By: Relevance
“…Several studies found increased cytotoxic CD8 T-cell activation and lower natural killer cell activity in HIV-infected individuals with clinical depression,13 14 while others found a higher risk of AIDS with increasing serum cortisol levels, a steroid hormone associated with depression 15 16. In contrast, one study in US veterans found no evidence of an association between depressive symptoms and mortality or AIDS-defining illness after adjustment for combination ART, while another, conducted prior to the availability of ART, found no association between depressive symptoms and accelerated mortality or worse medical outcome 3 17…”
Section: Introductionmentioning
confidence: 99%
“…Several studies found increased cytotoxic CD8 T-cell activation and lower natural killer cell activity in HIV-infected individuals with clinical depression,13 14 while others found a higher risk of AIDS with increasing serum cortisol levels, a steroid hormone associated with depression 15 16. In contrast, one study in US veterans found no evidence of an association between depressive symptoms and mortality or AIDS-defining illness after adjustment for combination ART, while another, conducted prior to the availability of ART, found no association between depressive symptoms and accelerated mortality or worse medical outcome 3 17…”
Section: Introductionmentioning
confidence: 99%
“…In a large cohort study of HIV-infected veterans, 34% had one or more psychiatric disease diagnoses [14]. It is estimated that approximately half of HIV-infected patients have major depressive symptoms and 20%–25% meet diagnostic criteria for a depressive disorder [15].…”
Section: Introductionmentioning
confidence: 99%
“…(Nurutdinova et al, 2012) Differences in present findings may reflect the differences in study populations. This sample of HIV infected Medicaid beneficiaries without SMI may be more disadvantaged and medically ill than the HIV-infected VA samples without SMI.…”
Section: Discussionmentioning
confidence: 64%
“…(Himelhoch et al, 2007); (Nurutdinova et al, 2012); (Walkup et al, 2010). This increased prevalence of SMI among individuals with HIV is thought to be secondary to the higher prevalence of substance abuse and HIV transmission risk behaviors, including unprotected sex and exchange sex among persons with SMI.…”
Section: Introductionmentioning
confidence: 99%